Structural Competency and the Medical Learning Environment—An Overdue Paradigm Shift in Medical Education - Iman F. Hassan; Rebecca Leeds; Ijeoma Nnodim Opara; Thuy D. Bui; Sharon E. Connor; Sejal Shah; Shwetha Iyer (Social Sciences, 2025)
Structural competency (SC) is a framework that assists clinicians in naming and analyzing the structural drivers that fundamentally contribute to morbidity and mortality. Undergraduate and graduate medical education is grounded in the experiential learning model where trainees learn through supervised, hands-on, real-world training and caring for patients within hospital and clinic settings. However, our present-day clinical settings fail to create a learning environment in which SC skills can be effectively taught and operationalized. The SC framework is designed to engender praxis, but to make this move upstream, healthcare institutions and medical education leaders need to do more to adapt their learning environment. We posit five elements and associated key actions that are essential to an SC learning environment: (1) the structural analysis of institutional policies and practices; (2) academic freedom and interdisciplinary discourse; (3) redefining medical education standards and metrics; (4) collective action to drive effect change; and (5) community integration and accountability.